THE CHOICE OF SURGICAL TREATMENT METHOD FOR DIABETES MELLITUS DEPENDS ON DESEASE ACTIVITY AND ITS COMPLICATIONS - T. I. Shraer (Вестник трансплантологии и искусственных органов)
Taking into consideration the treatment of 227 patients suffering from diabetes of I type on early stage, we consider a distal venous splenorenal anastomosis (DVSRA) to be an appropriate treatment method. Changing hormone regulation and influencing on metabolic processes, the given treatment is based on the research results. 2-nd (with nephritic syndrome) and 3-d (with progressive diabetic nephropathy) stages of diabetic nephropathy is the indication for kidney transplantation (KT). Combined KT and DVSRA proved to additionally improve a diabetes mellitus. GFR and creatinine level is not the only indication for KT, cardiovascular system failure, preliminary, is a major risk factor.